2014
DOI: 10.1183/09031936.00025214
|View full text |Cite
|
Sign up to set email alerts
|

The COPD assessment test: a systematic review

Abstract: The COPD assessment test (CAT) is a self-administered questionnaire that measures healthrelated quality of life. We aimed to systematically evaluate the literature for reliability, validity, responsiveness and minimum clinically important difference (MCID) of the CAT.Multiple databases were searched for studies analysing the psychometric properties of the CAT in adults with chronic obstructive pulmonary disease. Two reviewers independently screened, selected and extracted data, and assessed methodological qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
158
2
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(184 citation statements)
references
References 40 publications
13
158
2
11
Order By: Relevance
“…It is 5 years since the development and first validation of the COPD Assessment Test (CAT) [1], so the review of papers concerning the CAT by GUPTA et al [2] in this issue of the European Respiratory Journal is very timely. The authors identified over 40 studies using a systematic approach to minimise biases, although they acknowledge that they introduced one bias by selecting papers published only in English, French and Spanish, so eight papers were excluded.…”
Section: @Erspublicationsmentioning
confidence: 99%
“…It is 5 years since the development and first validation of the COPD Assessment Test (CAT) [1], so the review of papers concerning the CAT by GUPTA et al [2] in this issue of the European Respiratory Journal is very timely. The authors identified over 40 studies using a systematic approach to minimise biases, although they acknowledge that they introduced one bias by selecting papers published only in English, French and Spanish, so eight papers were excluded.…”
Section: @Erspublicationsmentioning
confidence: 99%
“…7 A systematic review supported the reliability and validity of the CAT and found that the tool is responsive to interventions, although the minimal clinically important difference (MCID) of 2 points is not well established. 8,9 Regarding the evolution of the CAT over time, only little data is available. 10 Our aim was to investigate the evolution of CAT in our THC cohort of COPD patients and to evaluate the potential of repeated CAT measurements to predict exacerbations.…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine the severity of symptoms, the GOLD guidelines suggest using instruments such as the modified Medical Research Council (mMRC) dyspnea scale, the Clinical COPD Questionnaire and the COPD Assessment Tool (CAT) [8,30,31].…”
Section: Stages Of Copdmentioning
confidence: 99%